The effect of two different speed endurance training protocols on a multiple shuttle run performance in young elite male soccer players - Vitale, J. A.; Povìa, V.; Vitale, N. D.; Bassani, T.; Lombardi, G.; Giacomelli, L.; Banfi, G.; La Torre, A. (Research in Sports Medicine, 2018)
There is not enough evidence on the impact of different speed endurance training regimes on footballers` ability to perform multiple shuttle run performance. This study examined the effect of 4 weeks of speed endurance maintenance (SEM) and speed endurance production (SEP) training on the 5-meter multiple shuttle run test (5-m MST) performance in young elite soccer players. A parallel two-groups, longitudinal design was used. Fifteen players were divided to either SEM (8 repetitions of 20-s all-out sprint interspersed with 40 s of recovery) or SEP (8 repetitions of 20-s all-out bout interspersed with 120 s of recovery) training group. SEM improved the ability to tolerate fatigue and maintained the performance development during the 5-m MST while SEP increased only the 1st sprint showing, simultaneously, an increased fatigue index and performance decrement. The selection of which training regimes to prioritize should be based on the players` characteristics and individual game requirements